2019
DOI: 10.1016/j.heliyon.2019.e01149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high temperature on pandemic and seasonal human influenza viral replication and infection-induced damage in primary human tracheal epithelial cell cultures

Abstract: High temperature reduces influenza viral replication; however, the treatment of fevers is thought to be necessary to improve patients' conditions. We examined the effects of high temperature on viral replication and infection-induced damage to human tracheal epithelial cells. Cell viability and dome formation were reduced, the number of detached cells was increased and lactate dehydrogenase (LDH) levels tended to be increased from 72 h to 120 h in uninfected cells cultured at 40 °C. Long-term (72 h and/or 120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Similar conclusions were reported by Molla et al while studying the effect of temperature on Poliovirus formation and RNA synthesis [154]. Yamaya et al, however, showed that, above 37 °C, the Influenza viruses' replication decrease [155], while Reed showed that for Panonychus-citri's nonoccluded virus, the biocidal temperature (above which the virus population is damaged) is 46 °C [156]. Chan, et al showed that for SARS-CoV, the biocidal temperature is <38 °C [157] and Harrison showed that Rothamsted Tobacco Necrosis virus biocidal temperature is even lower than Influenza's [158].…”
Section: Temperature Effect On Antiviral Activitysupporting
confidence: 83%
“…Similar conclusions were reported by Molla et al while studying the effect of temperature on Poliovirus formation and RNA synthesis [154]. Yamaya et al, however, showed that, above 37 °C, the Influenza viruses' replication decrease [155], while Reed showed that for Panonychus-citri's nonoccluded virus, the biocidal temperature (above which the virus population is damaged) is 46 °C [156]. Chan, et al showed that for SARS-CoV, the biocidal temperature is <38 °C [157] and Harrison showed that Rothamsted Tobacco Necrosis virus biocidal temperature is even lower than Influenza's [158].…”
Section: Temperature Effect On Antiviral Activitysupporting
confidence: 83%
“…According to the present review, KKT treatment increased body temperature, whereas the combination of gypsum and Ephedra herb decreased body temperature. High temperature reduced the replication of influenza A virus by affecting the function of acidic endosomes and inhibiting IL‐6‐mediated processes [70], which is mainly important during the acute phase of infection. On the other hand, a consistently high temperature can cause general malaise and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The influenza virus is internalised via receptor-mediated endocytosis, which requires an acidic environment for the endosome to trigger viral and endosomal membrane fusion[ 34 , 35 ]. High temperatures appear to increase endosomal pH, adversely affecting influenza virus entry and intracellular transportation[ 36 ].…”
Section: Effect Of Fever On Virusmentioning
confidence: 99%
“…While the viral messenger RNA transcription may be maintained at higher temperatures, genome replication is markedly reduced, due to reduced association of the polymerase with positive-sense RNA templates[ 41 ]. A raised temperature also appears to cause a reduction in the cytokine interleukin (IL)-6 levels after human cell infection with influenza virus[ 36 ]; IL-6 is required for a number of cytokine-mediated processes involved in viral replication[ 42 ].…”
Section: Effect Of Fever On Virusmentioning
confidence: 99%